The Relationship between Stress Levels and Premenstrual Syndrome in Nursing Students at Harapan Bangsa University - Nur Khoerotun Nisa; Siti Haniyah; Feti Kumala Dewi (LPPM Universitas Harapan Bangsa, 2023)
During the luteal phase of the menstrual cycle, which typically begins 7-10 days before menstruation and ends with menstruation, women of childbearing age often experience a collection of physical, behavioral, and emotional symptoms known as premenstrual syndrome (PMS). Stress levels are among the factors that can contribute to PMS. The objective of this study is to investigate the relationship between stress levels and PMS. This research employs a quantitative approach, using descriptive correlation methods and a cross-sectional design. The sample consisted of 62 respondents, selected through total sampling. Data were collected using a shortened Premenstrual Assessment Form (SPAF) questionnaire and the Perceived Stress Scale (PSS). Statistical analysis involved the Spearman Rank Test, which revealed a significant relationship between stress levels and PMS among Nursing Study Program students at Harapan Bangsa University Undergraduate Program. The p-value was 0.000, which is less than the significance level (α = 0.05), leading to the rejection of the null hypothesis (H0).The correlation coefficient (r) was calculated to be 0.456, indicating a moderate strength of correlation. This suggests that higher stress levels are associated with a greater perceived severity of PMS symptoms. Female students demonstrated an ability to both avoid stressors and manage stress, which can help reduce the occurrence of PMS symptoms